As instituições escolares de Cachoeira Dourada de Goiás: a interseção entre o público e o privado ( 1960-1971) - Ferreira, Élida Cristina Silva (2017)
The idea of schools as institutions has become an important field of historical research on education in Brazil. It offers a comprehensive view of educational processes (creation, operation and extinction of schools, architecture, furniture, practices, values, traditions etc.). However, it is likely that there may be gaps in this type of history study. For instance, schools with little representation in approaches and studies as well as studies on history of schools in certain states such as Goiás. This research refers to these two issues in taking as its subject the constitution of public and semi public schools in Cachoeira Dourada, state of Goiás, and broadens the list of categories of the history of schools. The research aimed to build a historical understanding of relations between Goiás and Brazilian governments in the circumstances of constitution and social, economic development of Cachoeira Dourada; the development of education in this city and the creation and functioning of three schools. This study relies on documental and empirical data. It troubles its subject historically in a qualitative and quantitative approach, besides following principles of Marxist dialectical method and being structured with derived from historical contextualization, specific bibliography reading, informal talks with Cachoeira Dourada’s residents and school community, visiting to archives, and development of pedagogical activity involving elementary students to gather records of Cachoeira Dourada’s past. Sources included house minutes and legislation (educational and non-educational), memoranda, newspaper stories, magazine articles, attendance books, manuscripts, student books and meeting minutes, among others. Bibliographical sources include memoir books, including of a former headmaster. Statistical data include educational and demographic numbers. Iconographic sources refer to photographs. Oral sources include informal conversations with former directors, former students, former teachers, and former school staff and Cachoeira Dourada older residents. The treatment of the sources followed procedures such as reading, summary making, note taking, data tabulation, description, organization of categories, among others. The research focused on time interval of I960 to 1971. Reading the history of education in Brazil and in Goiás together with the analysis of sources allows saying the beginnings of the history of Cachoeira Dourada and of its education link to interests much more political than educational. A peculiar situation arises: the coexistence of two types of public schools: one fully maintained by the municipality, the other maintained by a state-owned company in partnership with its service providers. The intersection between the public and the private in national education is visible in limits of school funding and structuring; teaching body composition; management and functioning; curricular guidelines; pedagogical and didactic practices; school ends. Regardless of whether it was public or partially private, schools in Cachoeira Dourada had a similar existence: of need and improvisation, of lack of material and human resources.